Initiation of multibeam sounding survey in the Japanese Antarctic Research Expedition - Izumi, Noriaki (2010)
The Japanese Antarctic Research Expedition was initiated in 1956. During the initial stage of the Expedition (between the 1st and 5th Expedition; from 1956 to 1960), preliminary bathymetric soundings were obtained along the transect between the Showa Station and Cape Town. From 1987, a full−scale mapping with a single beam echo sounder has started with an objective to make a nautical chart as well as a bathymetric map around the Showa Station, revealing the presence of deep continental shelf around the Antarctic. From 2009, SeaBeam 3020 was installed on the brand−new icebreaker Shirase (launched in 2009), starting the first swath mapping in the history of the Japanese Antarctic Research Expedition. The swath mapping data will be critical for generating the nautical and bathymetric charts in the Antarctic region, as well as for understanding the morpho−tectonics of the region. Published